Some Issues on the Adoption of in Rem Proceedings in the Republic of Armenia - Hovhannisyan, A.; Grigoryan, M. (Bulletin of Yerevan University C: Jurisprudence, 2020)
In the framework of this scientific article, the law on illicit property confiscation, which implements the in rem proceedings in RA, has been comprehensively examined. Analyzing the regulations of the law in the context of international documents, the case-law of the ECHR and the USA, and national legislation, many issues have been raised. Only in case of solving the aforementioned issues, the institute will serve the public good without endangering the protection of fundamental human rights and the principles recognized in states governed by the rule of law.